Fungal contamination and mycotoxins in aquafeed and tissues of aquaculture fishes and their biological control - Abdulfattah, Bashorun (2023)
The presence of mycotoxins in food and feed is a significant issue, especially in fish farming where it can negatively impact farmed fish species. In this study, samples of aquaculture feed and fishes tissues were collected for fungal isolation and mycotoxins analysis. Levels of aflatoxins (AFs) and ochratoxin A (OTA) in the muscles and organ (liver and kidneys) were compared in three fish species. Furthermore, the volatile organic compounds (VOCs) emitted from a novel Bacillus cereus BC344–2 strain were tested against the growth and mycotoxin production of Penicillium spp., Aspergillus spp., and Fusarium species. There was a moderate fungal load in the aquafeed with 1.30 × 102 ± 2.6 × 102 (mean ± SD) CFU/g with high contribution of Aspergillus and Penicillium fungi. OTA and AFs were detected in 95% and 66.7% of the tested aquafeed samples, respectively, with 66.7% of the samples co-contaminated with both mycotoxins. Although AFs contents were within permissible limits, 4.8% of samples showed OTA contamination exceeding the permissible limits (5 μg/kg). Both mycotoxins were found in the liver samples, but none of the fish meat (muscle) samples were found to be contaminated with OTA. The in vitro biocontrol co-incubation assay showed that BC344–2 VOCs had a significant inhibitory effect on the growth and sporulation of the three exposed fungi. P. verrucosum showed the highest sensitivity with a 42.4% inhibition ratio, followed by F. solani (17.5%) and A. flavus (11.5%). Additionally, BC344–2 VOCs suppressed OTA and AFs synthesis by P. verrucosum and A. flavus, respectively. Gas chromatography-based analysis of headspace volatiles in BC344–2 volatilome revealed five bioactive compounds with BTH aldehyde and 1-Heptadecanol being the most probable antifungal compounds responsible for the inhibitions. Given the high detection rate of OTA and AFs in the fish tissue and feed samples, along with regular monitoring of mycotoxins, the biocontrol approaches using bacterial volatiles such as BC344–2 VOCs could be useful to ensure feed and food safety.